Radiotheranostic Agents in Hematological Malignancies - Caers, Jo; Duray, Elodie; Vrancken, Louise; Marcion, Guillaume; Bocuzzi, Valentina; De Veirman, Kim; Krasniqi, Ahmet; Lejeune, Margaux; Withofs, Nadia; Devoogdt, Nick; Dumoulin, Mireille; Karlström, Amelie Eriksson; et al. (Frontiers in Immunology, 2022)
Radioimmunotherapy (RIT) is cancer treatment that combines radiation therapy with tumor directed monoclonal antibodies (Abs). Although RIT has been introduced for the treatment of CD20 positive non-Hodgkin lymphoma decades ago, it never found a broad clinical application. In recent years, researchers developed theranostic agents based on Ab fragments or small Ab mimetics such as peptides, affibodies or single-chain Abs with improved tumor-targeting capacities. Theranostics combines diagnostic and therapeutic capabilities into a single pharmaceutical agent and this dual application can be easily achieved after conjugation to radionuclides. The past decade has seen a growing trend to increased specificity, fastened pharmacokinetics and personalized medicine. In this review we discuss the different strategies that have been introduced for the non-invasive detection and treatment of hematological malignancies by radiopharmaceuticals. We also discuss future applications of these radiotheranostic agents.